Perception and Uses of Generative Artificial Intelligence in Relation to the Revised Bloom’s Taxonomy - Bolaños Carpio, Alexa (2025)
In recent years, Generative Artificial Intelligence (GAI) has experienced an explosive growth in everyday life, at work, and in academia. This research aims to identify the perceptions regarding the use of Generative Artificial Intelligence (GAI) among college students from the Atlantic Branch of the University of Costa Rica in 2024, and to describe these uses from a cognitive perspective through the relationship with the revised Bloom’s taxonomy. This study follows a quantitative design and approach. The survey was used as a data collection technique and the sample was selected using criteria of convenience and voluntary participation. The findings show that at the memory level students mainly use GAI to look up definitions of concepts (60.4%), whereas at the comprehension level to look up examples of information or concepts (63.5%). At the application level students use GAI to translate texts from Spanish into other languages; at the analysis level to solicit characteristics, properties, dimensions of a phenomenon (37.5%). At the evaluation level students primarily use GAI to correct the grammar of their own texts (43.8%), and at the creation level to produce brainstorms (50%). The conclusions suggest that students predominantly utilize GAI for lower-level cognitive processes like memorizing, comprehending and applying. Students also consider that they make an ethical use of GAI that enhances their academic progress. However, due to the novelty of the topic, it is necessary to continue researching in this area.